Functional neurologic disorders - Hallett, Mark, 1943-; Stone, Jon (Neurologist); Carson, Alan (Alan J.) (Handbook of clinical neurology, 2017)
"Functional Neurologic Disorders, the latest volume in the Handbook of Clinical Neurology series, summarizes state-of-the-art research findings and clinical practice on this class of disorders at the interface between neurology and psychiatry. This 51-chapter volume offers an historical introduction, chapters on epidemiology and pathophysiolology, a large section on the clinical features of different type of functional neurologic symptoms and disorders (including functional movement disorders, non-epileptic seizures, dizziness, vision, hearing, speech and cognitive symptoms), and then concluding with approaches to therapy. This group of internationally acclaimed experts in neurology, psychiatry, and neuroscience represent a broad spectrum of areas of expertise, chosen for their ability to write clearly and concisely with an eye toward a clinical audience. This HCN volume sets a new landmark standard for a comprehensive, multi-authored work dealing with functional neurologic disorders (also described as psychogenic, dissociative or conversion disorders)"--Publisher's description